Do rising class differentials in earnings increase productivity? Evidence for non-production and production employees in U.S. manufacturing industries. (September 2016) - Guven, Aytekin; Sakamoto, Arthur
Highlights: Quantitative sociological research rarely investigates productivity but it is pertinent to the study of inequality and social stratification. We focus on the earnings differential between non-production and production employees and evaluate its net effect on productivity in the U.S. Contrary to assumptions of traditional economics, this earnings differential had a negative effect on productivity The rising earnings differential between non-production and production employees does not inexorably enhance economic efficiency. This rising earnings differential partly derives from changes in the relative bargaining power of these two class categories in the labor market. Abstract: Quantitative sociological research rarely investigates productivity but it is pertinent to the study of inequality and social stratification. In this analysis, we focus on the earnings differential between non-production and production employees and evaluate the extent to which it has a net effect on productivity across U.S. manufacturing industries. Contrary to assumptions of traditional economics, the findings indicate that this earnings differential increased significantly since the 1980's but actually had a negative effect on productivity. There is also some evidence that this effect has become more negative in recent years. We interpret these findings as suggesting that, rather than inexorably enhancing economic efficiency, rising earnings differentials between non-production and production employees partly derive from changes in the relative bargaining power of these two class categories in the labor market.